The distribution of anionic sites on the surface of the Golgi complex (The Rockefeller University Press, 1976)
The distribution of anionic binding sites has been investigated in the isolated Golgi complex using cationic ferritin. The greatest density of anionic sites occurs on the tubular network and small vesicles, and this binding is accompanied by increased levels of galactosyltransferase activity. The density of anionic sites on the cisternae is less than on the tubules and shows anisotropic distribution, with higher density on the convex surface and lower density on the concave surface. The distribution of anionic sites may reflect the functional activity of the Golgi complex and possibly the interaction or cohesion between cisternae in this organelle.